Urban Island Modeling for Semi-Arid Cities: The Case of the City of Oujda - Djebbour Mounir; Sbai Abdelkader (E3S Web of Conferences)
There is often a difference between the surface temperature and the various types of land use within cities, where it rises in built-up areas and barren lands and decreases in areas with vegetation cover and dense afforestation. In this study, the urban heat island phenomenon was analyzed by linking the relationship between the different types of land use in the city of Oujda and the surface temperature based on Landsat imagery and some indicators. These indicators include the Normalized Difference Vegetation Index (NDVI), which measures the health and density of vegetation, and the Land Surface Temperature (LST), which provides a direct measurement of the temperature of the land surface. The results showed variations in the surface temperature of the city of Oujda, which rises in areas with a low level of afforestation and vegetation cover, as well as in built-up areas, the industrial district, and barren lands. In contrast, the surface temperature of the land decreases in areas with an increase in vegetation cover. This study found that the impact of the surface temperature varies according to the nature of land use, vegetation cover, and other factors. It highlighted the importance of geographic information systems and remote sensing in studying climate changes and revealing the importance of vegetation cover in reducing this phenomenon.